Mechanisms of Cell Death in Acute Liver Failure - Bantel, Heike (Frontiers in Physiology, 2012)
Acute liver failure (ALF) can be the consequence of various etiologies, that might vary between different geographic regions. Most frequent are intoxications with acetaminophen, viral hepatitis, or liver damage of unknown origin. ALF occurs when the extent of hepatocyte death exceeds the regenerative capacity of the liver. The mode of liver cell death that is predominantly induced in ALF, i.e., apoptosis or necrosis, is still controversial and presumably determined by the etiology, duration, and magnitude of liver injury. Severe liver damage involves oxidative stress and depletion of ATP resulting in necrosis. In contrast, maintenance of ATP stores is required for the execution of apoptosis. Recent data suggest that necrosis resulting from severe liver damage is associated with poor outcome of ALF patients. Discrimination between apoptosis and necrosis might be therefore useful for the identification of ALF patients requiring liver transplantation. Identification of the molecular cell death mechanisms remains an important issue not only for early prediction of ALF outcome, but also for therapeutic interventions. In view of the pleiotropic functions of critical mediators of cell death and tissue regeneration, a particular challenge will be to reduce hepatocellular death without inhibiting the regenerative capacity of the liver. Here, we review the molecular mechanisms of hepatocyte injury and the pathways leading to apoptosis and necrosis, which might represent potential diagnostic and therapeutic targets in ALF.